(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2025)
This research attempts to approach the manifestations of the intellectual’s personality in the Syrian Arab novel in the second half of the twentieth century, based on the importance of the personality element in the architecture of the novel as a literary genre, and the role of this element in providing the novel with one of the most important components of the artistic structure, and the aesthetics of this structure; The study of the character of the intellectual in the Syrian Arab novel has intellectual and artistic dimensions, due to the possibility of a connection between the novel as a literary art and its social and cultural references. The research focused on studying the educated character in the Syrian novel that deals with the Syrian Arab countryside by a group of Syrian novelists. Then the research tested the effectiveness of the educated character in the rural novel, through three basic models, which are: (the traditional intellectual, the revolutionary intellectual, and the non-affiliated intellectual), with the aim of Forming a general view of the character of the intellectual in the Syrian Arab novel, to extract its general vision, and study its characters, in order to reveal its aesthetics, and shed light on its role and the extent of its ability to transfer the Syrian Arab novel from the shades of romanticism to realism.